Pengutamaan Nilai Religiusitas Dalam Usaha (Studi Atas Pengusaha Madura) - Iskandar .; Khoirul Asiah (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This study aims to describe the phenomenon of prioritizing religious values in business and entrepreneurial practices among Madurese entrepreneurs, as well as to identify the driving factors underlying this prioritization. This research employs a descriptive-analytical design with a qualitative approach. The data were obtained through an in-depth analysis of empirical phenomena occurring in the field, using both structured and unstructured interviews, supported by observation and documentation to strengthen data validity. The findings reveal that the prioritization of religious values by Madurese entrepreneurs in the business sector constitutes a unique and factual phenomenon that is relatively rarely found among other ethnic communities. Religious values are not merely positioned as personal beliefs but are internalized in work ethics, business decision-making, and socio-economic relations. The driving factors behind the prioritization of religious values include strong religious conviction, the dominance of Islamic teachings in social life, deeply rooted religious traditions and culture, a strong work ethic, Madurese local wisdom, a religious social environment, the application of Islamic business ethics, and the perception of business activities as preparation for the afterlife. Overall, this phenomenon originates from a harmonious integration of Islamic teachings and local wisdom that has been deeply embedded in Madurese culture.